ON THE ICONOGRAPHY OF LIONS AND LEOPARDS ON THE GOBLET OF KARASHAMB - Амаякян, Асмик Арутюновна; Мирзоян, Моника Овиковна (History, Archeology and Ethnography of the Caucasus, 2024)
The Goblet of Karashamb (c. 22nd-21st centuries BC, stored in the History Museum of Armenia, HMA 3183-206) is considered one of the most renowned archaeological artifacts in Armenia. The iconographic features of the goblet have already been discussed by researchers. Various opinions, parallels, and comparisons mentioned by them highlight that the Goblet of Karashamb synthesizes the iconography and jewelry styles distinctive to Mesopotamia, Asia Minor, and the South Caucasus. While concurring with this assessment, this study focuses specifically on the depictions of lions and leopards on the goblet, exploring potential parallels in Asia Minor culture. For the first time, these depictions are examined within the context of preserved Hittite sources, correlating their role with the attributes and proceedings of the Hittite KI.LAM festival (the “Festival of the Gate”) of Hattian origin. Certain aspects of the Goblet of Karashamb’s iconography suggest connections to early Hittite or pre-Hittite periods. The iconography of lions and leopards represents an ancient tradition in Asia Minor, exemplified by the Lion Gate of Hattusa. A notable instance of royal association with these animals appears in the Annals of Ḫattušilis I (c. 1650-1620 BCE), one of the earliest Hittite kings. The analyzed attributes of the KI.LAM festival, contextualized within the goblet’s iconography, have ancient Hattian roots and likely trace back to the early Hittite period. This interpretation is further supported by Anitta’s text (c. 1790-1750 BCE) from the early Hittite period, which scholars have compared to the KI.LAM festival description. Notably, the animals captured during the royal hunt in this text correspond to those depicted on the Goblet of Karashamb.